THE ERROR ANALYSIS OF STUDENTS' PRONUNCIATION OF ENGLISH VOWEL - Ningsih Ningsih; Mulyadi Mulyadi; Rizka Indahyanti (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2024)
The objective of this research was to find out the kinds of students’ errors in pronunciation English vowels at UPT SMA Negeri 14 Maros and to know the causes of students’ errors in pronunciation English vowel of the students at UPT SMA Negeri 14 Maros. It employs a qualitative descriptive approach, with class X.4 students as the subjects. Data collection used oral tests and interview. The pronunciation errors of English vowels by students at UPT SMA Negeri 14 Maros were influenced by several factors. The first factor was the students' first language, which led to habitual errors through imitation, mishearing, or mispronunciation. Another factor was carelessness, which was often linked to a lack of motivation. The most mispronounced diphthongs were /e?/, /a?/, and /au/. The researcher concluded that these diphthongs had the highest error rates among the students. The researcher found most of students made error in pronounce diphthong /e?/ with frequency 64 errors. The second level of error was / a? / with 63 errors. The last is diphthong /au/ with 39 errors It seem that the students still not approprite on use diphthong pronounciation correctly.